Higher education journals: their characteristics and contribution. Issue 3 (16th April 2018) - Tight, Malcolm
ABSTRACT: The study of higher education journals – that is, refereed academic journals wholly focused on higher education – reveals much about the field of higher education research. This analysis identified 86 such journals published in the English language, considering their focus, ownership, location, orientation, age, size and ranking. From this analysis, a shorter list of 28 key journals is identified. It is argued that, given the scale of the contribution being made to higher education research – for example, the 86 journals between them published over 16, 000, 000 words in 2016, with this total increasing year on year – it may be time to spend more effort on synthesising and disseminating what we have already learnt, rather than, or before, undertaking fresh research.